Global health, global surgery and mass casualties. I. Rationale for integrated mass casualty centres. Issue 6 (22nd December 2019) - Khan, Tariq; Quintana, Leonidas; Aguilera, Sergio; Garcia, Roxanna; Shoman, Haitham; Caddell, Luke; Latifi, Rifat; Park, Kee B; Garcia, Patricia; Dempsey, Robert; Rosenfeld, Jeffrey V; Scurlock, Corey; et al.
Abstract : It has been well-documented recently that 5 billion people globally lack surgical care. Also well-documented is the need to improve mass casualty disaster response. Many of the United Nations (UN) Sustainable Development Goals (SDGs) for 2030—healthcare and economic milestones—require significant improvement in global surgical care, particularly in low-income and middle-income countries. Trauma/stroke centres evolved in high-income countries with evidence that 24/7/365 surgical and critical care markedly improved morbidity and mortality for trauma and stroke and for cardiovascular events, difficult childbirth, acute abdomen. Duplication of emergency services, especially civilian and military, often results in suboptimal, expensive care. By combining all healthcare resources within the ongoing healthcare system, more efficient care for both individual emergencies and mass casualty situations can be achieved. We describe progress in establishing mass casualty centres in Chile and Pakistan. In both locations, planning among the stakeholders (primarily civilian and military) indicates the feasibility of such integrated surgical and emergency care. We also review other programmes and initiatives to provide integrated mass casualty disaster response. Integrated mass casualty centres are a feasible means to improve both day-to-day surgical care and mass casualty disaster response. The humanitarian aspect of mass casualty disasters facilitates integration among stakeholders—from local healthcare systems to military resources to international healthcare organisations. The benefits of mass casualty centres—both healthcare and economic—can facilitate achieving the 2030 UN SDGs.